Study of Weeds as Traditional Medicinal Plants Used by Indigenous People of West Pasaman, Indonesia - Rizki, Rizki; Nursyahra, Nursyahra; Fernando, Oki (Journal of Tropical Horticulture, 2019)
Ethnobotanical study of weeds as traditional medicinal plants was conducted in West Pasaman,Â  Indonesia. Weed is a type of wild plant that grows naturally without deliberately planted by humans. Weeds grow around housing residents or farmlands. Their existence is less desirable, but indigenous people in Luhak Nan Tigo, West Pasaman, utilize some types of weeds as traditional medicinal plants. This study was focused on identifying weeds as medicinal plants, disease treated, part of the weeds used, methods of preparation, and ingredients added. The descriptive survey method with observation and interview techniques was employed in this study. A total of 35 species of weeds belonging to the 23 plants family were identified. Weeds are used as traditional medicines to cure wounds, fever, bone pain, abdominal pain, back pain, itching, heartburn, asthma, and phlegm.